Solar cell and preparation method thereof
By doping copper in the TCO film layer and controlling the grain size, the problem of insufficient binding force between the gate line and the TCO film layer in the solar cell is solved, and higher photoelectric conversion efficiency and conductive performance are achieved.
Patent Information
- Application Number
- CN202510096652.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
AI Technical Summary
In the field of solar cells, the bonding force between the gate line and the TCO film layer is poor, which causes the gate line to fall off easily, affecting the photoelectric conversion efficiency and conductivity of the solar cell.
By doping copper in the TCO film layer, at least 95% of the grain size in the TCO film layer is controlled to be 15nm to 35nm, ensuring effective doping of copper in the TCO film layer, avoiding excessive accumulation of copper at the grain boundaries, thereby improving the binding force between the gate line and the TCO film layer.
While maintaining the excellent overall performance of the TCO film layer, it effectively improves the binding force between the gate line and the TCO film layer, and improves the photoelectric conversion efficiency and conductivity of solar cells.
Smart Images

Figure CN119923025A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a solar cell and a preparation method thereof. Background Art
[0002] In the field of solar cells, the bonding between the gate wire and the TCO film is poor, and the gate wire is easy to fall off. Therefore, a common method is to dope elements in the TCO film to improve the bonding between the gate wire and the TCO film. However, different doping elements have different degrees of difficulty in doping in the TCO film; at the same time, the size of the grains in the TCO film will also affect the diffusion of the doping elements in the TCO film.
[0003] Specifically, the TCO film is a polycrystalline layer with a grain size of hundreds of nanometers. The smaller the grain size in the TCO film layer, the more corresponding grain boundaries there are. The grain boundaries are fast channels for the diffusion of doping elements. The more grain boundaries there are, the easier it may be to inject doping elements into the TCO film layer. However, this may also easily lead to the accumulation of doping elements at the grain boundaries, affecting the overall performance of the TCO film layer (including electrical properties, optical properties, mechanical properties and corrosion resistance, etc.).
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a solar cell and a preparation method thereof, so as to solve or improve the above-mentioned technical problems, realize the effective doping of copper in the TCO film layer, avoid excessive accumulation of copper at the grain boundary, and further effectively improve the bonding force between the gate line and the TCO film layer while ensuring that the TCO film layer has excellent overall performance, which is conducive to making the solar cell have both better photoelectric conversion efficiency and conductive performance.
[0006] The present invention can be implemented like this:
[0007] In a first aspect, the present invention provides a solar cell, the solar cell comprising a cell substrate, the cell substrate comprising a first surface and a second surface opposite to the first surface;
[0008] The solar cell further comprises a TCO film layer located on the first surface and / or the second surface, the TCO film layer contains copper; at least 95% of the grains in the TCO film layer have a size of 15nm to 35nm.
[0009] In an optional embodiment, the TCO film layer contains at least <222> Grain orientation; and, in the TCO film layer, <222> The intensity of the diffraction peak corresponding to the grain orientation is the strongest.
[0010] In an optional embodiment, in the TCO film layer, <222> The grain-oriented grains account for 70 wt% to 80 wt%.
[0011] In an optional embodiment, the TCO film layer further comprises <440> Grain orientation and <622> Grain orientation;
[0012] <222> Grain orientation, <440> Grain orientation and <622> The total proportion of grains corresponding to the grain orientation in the TCO film layer is not less than 90wt%.
[0013] In an optional embodiment, in the TCO film layer, <440> The diffraction peak intensity corresponding to the grain orientation is <222> 1 / 6 to 1 / 3 of the diffraction peak intensity corresponding to grain orientation;
[0014] or, <622> The diffraction peak intensity corresponding to the grain orientation is <222> The diffraction peak intensity corresponding to the grain orientation is 1 / 6 to 1 / 3.
[0015] In an optional embodiment, the concentration of copper in the 5 nm depth range of the TCO film layer from the surface of the TCO film layer to the battery substrate is 1×10 18 ions / cm 2 ~1×10 21 ions / cm 2 ;
[0016] Or, along the direction from the surface of the TCO film to the battery substrate, within the depth range of 20nm to 25nm of the TCO film, the concentration of copper is 1×10 10 ions / cm 2 ~1×10 14 ions / cm 2 ;
[0017] Or, along the direction from the surface of the TCO film to the battery substrate, within the depth range of 30nm to 50nm of the TCO film, the copper concentration is ≤1×10 5 ions / cm 2 ;
[0018] Alternatively, along the direction from the surface of the TCO film layer to the battery substrate, the depth of copper in the TCO film layer does not exceed 50 nm.
[0019] In an optional embodiment, the surface roughness of the TCO film layer on the side away from the battery substrate is 20 nm to 30 nm.
[0020] In an optional embodiment, at least the grain boundary gaps within the TCO film layer are bonded with copper through bonding.
[0021] In an optional embodiment, the thickness of the TCO film layer is 50 nm to 150 nm.
[0022] In an optional embodiment, a metal seed layer is disposed at a position corresponding to the gate line region on a side of the TCO film layer away from the battery substrate.
[0023] In an optional embodiment, the solar cell further includes a doping layer disposed between the cell substrate and the TCO film layer, and a grid line connected to the metal seed layer.
[0024] In an optional embodiment, the solar cell includes a cell substrate;
[0025] A first passivation layer and a first doping layer are stacked on the front side of the battery substrate; a first TCO film layer is arranged on the front side of the doping layer, and a first metal seed layer is arranged on the front side of the first TCO film layer at a position corresponding to the gate line region; and a first gate line is connected to the front side of the first metal seed layer;
[0026] A second passivation layer and a second doping layer are stacked on the back of the battery substrate; a second TCO film layer is arranged on the back of the second doping layer, and a second metal seed layer is arranged on the back of the second TCO film layer at a position corresponding to the gate line area; and a second gate line is connected to the back of the second metal seed layer.
[0027] In a second aspect, the present invention provides a method for preparing a solar cell according to any one of the aforementioned embodiments, comprising the following steps:
[0028] A copper-containing TCO film layer is disposed on the first surface and / or the second surface of the battery substrate.
[0029] In an optional embodiment, the following steps are included:
[0030] Disposing a copper-containing TCO film layer on the first surface and / or the second surface of the battery substrate;
[0031] A metal seed layer is disposed on the side of the TCO film layer away from the battery substrate.
[0032] In an optional embodiment, the following steps are included:
[0033] A first passivation layer and a first doping layer are stacked on the first surface of the battery substrate; a first TCO film layer is disposed on the front of the first doping layer, and a first metal seed layer is disposed on the front of the first TCO film layer; and a first gate line is connected to the front of the first metal seed layer;
[0034] A second passivation layer and a second doping layer are stacked on the second surface of the battery substrate; a second TCO film layer is disposed on the back of the second doping layer, and a second metal seed layer is disposed on the back of the second TCO film layer; and a second gate line is connected to the back of the second metal seed layer.
[0035] The beneficial effects of the present invention include:
[0036] In the present invention, copper is doped in the TCO film layer. On the one hand, the atomic size of copper is moderate, which is conducive to its diffusion in the solid material (TCO film layer); on the other hand, copper has moderate electronegativity, and forms weak chemical bonds with indium oxide, tin oxide or other elements in the TCO film layer, making it easier to diffuse in the TCO film layer. In contrast, copper has a higher diffusion coefficient in the TCO film layer than other metal elements (such as nickel, tungsten, titanium, silver, etc.), and can not only be doped on the surface of the TCO film layer, but also further doped into the grain boundary gaps of the TCO film layer. Based on the fact that copper is easier to diffuse in the TCO film layer than other doping elements, the present invention specifically controls at least 95% of the grain size in the TCO film layer to be 15nm to 35nm. Under this grain size and content, it can ensure the effective doping of copper in the TCO film layer while avoiding excessive accumulation of copper at the grain boundary, thereby effectively improving the bonding force between the gate line and the TCO film layer while ensuring that the TCO film layer has excellent overall performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 A schematic diagram of the structure of a solar cell (HJT cell) provided in Example 1;
[0039] Figure 2 The XRD pattern of the first TCO film layer in the solar cell provided in Example 1;
[0040] Figure 3 The XRD pattern of the second TCO film layer in the solar cell provided in Example 1;
[0041] Figure 4 The SEM image of the solar cell provided in Example 1;
[0042] Figure 5 for Figure 4 The enlarged picture of the box in the middle;
[0043] Figure 6 This is a graph showing the corrosion resistance test results of the yellow film prepared in Example 7 provided in Test Example 2.
[0044] Icon: 100-battery substrate; 111-first intrinsic amorphous silicon layer; 112-N-type doped layer; 113-first TCO film layer; 114-first copper seed layer; 115-first gate line; 116-first protective layer; 121-second intrinsic amorphous silicon layer; 122-P-type doped layer; 123-second TCO film layer; 124-second copper seed layer; 125-second gate line; 126-second protective layer. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0046] The solar cell and the preparation method thereof provided by the present invention are described in detail below.
[0047] The test method involved in the present invention includes:
[0048] ①. Use secondary ion mass spectrometry (SIMS) to detect copper doping concentration;
[0049] ② Use scanning electron microscope (SEM) to detect the layer structure;
[0050] ③. Use X-ray diffractometer to perform XRD detection, including analysis of grain orientation, diffraction peak intensity, grain content and size, etc.;
[0051] The calculation method of the grain size is based on the Scherrer formula. Specifically, the expression is D = Kλ / βcosθ. 123 Where D is the grain size in nm; K is a constant whose value is determined by β. When β is the half-height width of the diffraction peak, K = 0.89; when β is the half-height width of the diffraction peak area integration, K = 1; λ is the wavelength of the X-ray in nm; β is the half-height width of the diffraction peak in radians; θ is the diffraction angle.
[0052] ④. Use atomic force microscopy to perform AFM testing, including testing the surface morphology and roughness of the material;
[0053] ⑤. Use a thrust meter to detect the bonding force between the TCO film layer and the copper seed layer in the gate line area;
[0054] ⑥. Use IV tester to test the electrical parameters of the battery cell.
[0055] The present invention provides a solar cell, which includes a cell substrate, the cell substrate includes a first surface and a second surface opposite to the first surface, and the solar cell also includes a TCO film layer located on the first surface and / or the second surface, the TCO film layer contains copper; at least 95% of the grains in the TCO film layer have a size of 15nm to 35nm.
[0056] The battery substrate may be a silicon-based substrate, for example.
[0057] The TCO film layer is a transparent conductive oxide film layer, which can collect the current generated by the photoelectric effect. The performance of the TCO film layer directly affects the efficiency and stability of the solar cell, such as transparency, conductivity and durability. In the present invention, the material of the TCO film layer can exemplarily but not limitatively include ZnO, SnO2 and ITO (such as silver indium oxide).
[0058] In the present invention, a metal seed layer is disposed at a position corresponding to the gate line region on a side of the TCO film layer away from the battery substrate, and the metal in the metal seed layer may exemplarily include at least one of silver, copper, nickel, titanium, tantalum, tungsten and aluminum. In some typical embodiments, the metal seed layer may be a copper seed layer.
[0059] The metal seed layer can provide good conductivity in solar cells, help form an efficient current collection network, and improve the overall performance of solar cells.
[0060] Furthermore, the solar cell further comprises a doping layer disposed between the cell substrate and the TCO film layer, and a grid line connected to the metal seed layer.
[0061] Furthermore, the solar cell also includes a protection layer for protecting the grid lines, such as a tin protection layer. In addition, a protection layer made of other materials may also be provided as required.
[0062] In some embodiments, the first surface or the second surface of the solar cell has a TCO film layer, and the TCO film layer contains copper. In other embodiments, both the first surface and the second surface of the solar cell have a TCO film layer, and the TCO film layer contains copper.
[0063] In some embodiments, 95%, 96%, 97%, 98% or 99% of the grains in the TCO film may have a size of 15nm to 35nm. In addition, the grain size corresponding to other values in the range of not less than 95% in the TCO film may be 15nm to 35nm. In some preferred embodiments, at least 95% of the grains in the TCO film have a size of 18nm to 25nm.
[0064] In the present invention, copper is doped in the TCO film layer. On the one hand, the atomic size of copper is moderate, which is conducive to its diffusion in the solid material (TCO film layer); on the other hand, copper has moderate electronegativity, and the chemical bond formed with indium oxide, tin oxide or other elements in the TCO film layer is weak, making it easier to diffuse in the TCO film layer. In contrast, copper has a higher diffusion coefficient in the TCO film layer than other metal elements (such as nickel, tungsten, titanium, silver, etc.), and can be doped not only on the surface of the TCO film layer, but also further doped into the grain boundary gaps of the TCO film layer. It should be noted that, generally, there are a large number of pits and protrusions on the TCO surface (that is, the surface of the TCO film layer has a certain degree of roughness or gaps). In some embodiments of the present invention, copper mainly exists in the gaps on the surface of the TCO film layer; in other embodiments of the present invention, copper exists on the surface and inside of the TCO film at the same time. The bonding effect of copper atoms and / or copper ions with the chemical bonds in the TCO film layer is conducive to further improving the bonding force between the TCO film layer and the metal seed layer. In some optional embodiments, at least the grain boundary gaps within the TCO film layer are bonded with copper through bonding.
[0065] It should be noted that the grain size in the TCO film layer will affect the copper injection concentration, which is mainly reflected in the following aspects:
[0066] ①, Grain boundary effect: TCO film is a polycrystalline layer with a grain size of hundreds of nanometers. The smaller the grain size, the more grain boundaries there are. Grain boundaries are fast channels for atomic diffusion, so copper atoms may be more easily injected into the TCO film layer through grain boundaries. However, this may also cause copper atoms to accumulate at the grain boundaries, affecting the overall performance of the TCO film layer.
[0067] Among them, the accumulation of copper atoms at the grain boundaries affects the overall performance of the TCO film mainly in the following aspects:
[0068] A. Electrical properties: The accumulation of copper atoms at the grain boundaries may cause the resistivity of the TCO film to change, thus affecting its conductivity. The accumulated copper atoms may form conductive channels or produce electrochemical effects, leading to an increase in local current density and even causing short circuits.
[0069] B. Optical performance: TCO films are usually required to have high light transmittance, and the accumulation of copper atoms at the grain boundaries may affect the transmittance of light. The accumulated copper atoms may absorb or scatter light, resulting in a decrease in the optical performance of the TCO film.
[0070] C. Mechanical properties: The accumulation of copper atoms at the grain boundaries may also affect the mechanical properties of the TCO film. The grain boundary is the weak link of the metal material, and the accumulated copper atoms may increase the brittleness of the grain boundary, making the TCO film more likely to break or damage when subjected to external forces.
[0071] D. Corrosion resistance: The accumulation of copper atoms at the grain boundaries may also affect the corrosion resistance of the TCO film. The accumulated copper atoms may form a galvanic effect, making the TCO film more susceptible to corrosion damage in a humid or corrosive environment.
[0072] Therefore, when preparing the TCO film layer, it is necessary to reasonably control the injection amount and distribution of copper atoms to avoid excessive accumulation at the grain boundaries, thereby ensuring that the TCO film layer has excellent overall performance.
[0073] ② Carrier transport: Grain size also affects carrier transport in the TCO film. Larger grains usually mean less grain boundary scattering, which is beneficial to carrier migration. If the injection of copper atoms causes a significant decrease in carrier mobility, the conductive properties of the TCO film may be affected.
[0074] ③. Film quality: Grain size is also an important indicator for measuring TCO film quality. Smaller grains may lead to increased film surface roughness, thereby affecting the injection efficiency and distribution uniformity of copper atoms.
[0075] As mentioned above, the grain size in the TCO film layer indirectly affects the concentration of copper injected into the TCO film layer by affecting the number of grain boundaries, carrier transport and film quality. The present invention specifically controls at least 95% of the grain size in the TCO film layer to be 15nm to 35nm. Under this grain size and content, it can ensure the effective doping of copper in the TCO film layer while avoiding excessive accumulation of copper at the grain boundaries, thereby effectively improving the bonding force between the gate line and the TCO film layer while ensuring that the TCO film layer has excellent overall performance.
[0076] In some optional embodiments, the TCO film layer contains at least <222> Grain orientation; and, in the TCO film layer, <222> The intensity of the diffraction peak corresponding to the grain orientation is the strongest.
[0077] It should be noted that the grain orientation of the TCO film mainly grows in the orientation with the lowest energy consumption; <222> The oriented grains are perpendicular to the direction in which the metal seed layer bombards the battery substrate, that is, the metal ions or metal atoms bombard the battery substrate vertically. <222> This can inhibit excessive copper accumulation and thus limit copper diffusion, so as to form uniform copper doping. In the TCO film layer, the more grains there are, the stronger the corresponding diffraction peak. In the present invention, the TCO film layer <222> The intensity of the diffraction peak corresponding to the grain orientation is the strongest, which can ensure the effective formation of uniform copper doping.
[0078] In some optional embodiments, in the TCO film layer, <222> The proportion of grains with grain orientation is 70wt% to 80wt%, such as 70wt%, 71wt%, 72wt%, 73wt%, 74wt%, 75wt%, 76wt%, 78wt%, 79wt% or 80wt%, etc., and can also be other values within the range of 70wt% to 80wt%.
[0079] In order to make copper uniformly doped in the TCO film layer, the present invention adds <222> The oriented grains are set to be the largest. Specifically, the TCO film layer <222> The grain proportion of grain orientation is set to 70wt% to 80wt%, which can improve the uniformity of copper doping on the one hand, and minimize the damage to the light transmission performance of TCO on the other hand. In addition, it is also beneficial to improve the conductivity of the TCO film layer.
[0080] In some optional embodiments, the TCO film layer further comprises <440> Grain orientation and <622> Grain orientation; <222> Grain orientation, <440> Grain orientation and <622> The total proportion of grains corresponding to the grain orientation in the TCO film layer is not less than 90wt%. In other words, <222> Grain orientation, <440> Grain orientation and <622> The total proportion of other grains other than the grains corresponding to the grain orientation in the TCO film layer does not exceed 10wt%, such as 10wt%, 9wt%, 8wt%, 7wt%, 6wt%, 5wt%, 4wt%, 3wt%, 2wt% or 1wt%, etc., or other values not exceeding 10wt%.
[0081] Above <440> Grain orientation and <622> Grain orientation and <222> The grains grow together in an oriented manner. <222> During the growth of oriented grains, the main incidental growth <440> and <622> Oriented grains may also be accompanied or co-produced with other less oriented grains (such as <211> Oriented grains, <332> Oriented grains and <400> oriented grains).
[0082] because <440> , <622> and <222> The orientations of the grains are relatively close, so the grains with the above orientations can all play a role in inhibiting copper diffusion. <440> as well as <222> The orientation difference gradually becomes larger, and the corresponding inhibition effect gradually becomes worse.
[0083] The present invention is achieved by <222> Grain orientation, <440> Grain orientation and <622> The total proportion of grains corresponding to the grain orientation in the TCO film layer is controlled to be no less than 90wt%, which can facilitate the injection of copper; at the same time, it is also beneficial to prevent and improve the possible weakening of the optical properties of TCO after copper injection, and avoid the reduction of the short-circuit current of the battery cell.
[0084] In some optional embodiments, in the TCO film layer, <440> The diffraction peak intensity corresponding to the grain orientation is <222> The diffraction peak intensity corresponding to the grain orientation is 1 / 6 to 1 / 3, such as 1 / 6, 1 / 5, 1 / 4 or 1 / 3, etc., and may also be other values within the range of 1 / 6 to 1 / 3.
[0085] In some optional embodiments, <622> The diffraction peak intensity corresponding to the grain orientation is <222> 1 / 6 to 1 / 3 of the diffraction peak intensity corresponding to the grain orientation, such as 1 / 6, 1 / 5, 1 / 4 or 1 / 3, etc., or other values within the range of 1 / 6 to 1 / 3. In some typical implementations, <622> The diffraction peak corresponding to the grain orientation is the third most intense diffraction peak.
[0086] For the sake of distinction, the following definition of TCO film layer is given: <222> The diffraction peak corresponding to the grain orientation is the first X-ray diffraction peak. <440> The diffraction peak corresponding to the grain orientation is the second X-ray diffraction peak. <211> The diffraction peak corresponding to the grain orientation is the third X-ray diffraction peak. <400> The diffraction peak corresponding to the grain orientation is the fourth X-ray diffraction peak. <332> The diffraction peak corresponding to the grain orientation is the fifth X-ray diffraction peak. <431> The diffraction peak corresponding to the grain orientation is the sixth X-ray diffraction peak. <622> The diffraction peak corresponding to the grain orientation is the seventh X-ray diffraction peak.
[0087] In some embodiments, a first TCO film layer is provided on the front side of the battery substrate, and in the first TCO film layer, the intensity of the seventh X-ray diffraction peak is greater than the intensity of the fourth X-ray diffraction peak. In some embodiments, a second TCO film layer is provided on the back side of the battery substrate, and in the second TCO film layer, the intensity of the seventh X-ray diffraction peak is less than the intensity of the fourth X-ray diffraction peak.
[0088] It should be noted that if <440> Grain and <622> The peak intensity of the radiation corresponding to the grain orientation exceeds <222> The peak intensity of the emission corresponding to the grain orientation is 1 / 6 to 1 / 3, which means <222> The reconstruction, stacking, dislocation and other abnormalities of the grains will not only prevent the uniform diffusion of copper, but also affect the permeability and conductivity of the TCO film layer.
[0089] As mentioned above, the TCO film layer in the present invention has a high degree of crystallinity, a sharp and high-intensity diffraction peak, and a large crystal grain size (15nm to 35nm), which is more conducive to the effective injection of copper. At the same time, the high degree of crystallinity is more conducive to preventing and improving the possible weakening of the optical properties of TCO after copper injection, and avoiding the reduction of the short-circuit current of the battery cell. In addition, the high degree of crystallinity and the large grain size are also conducive to improving the process window of copper electroplating and preventing the TCO film layer from being corroded by the acid solution of the copper electroplating process.
[0090] In some optional embodiments, the thickness of each TCO film layer can be 50nm to 150nm, such as 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm, 115nm, 120nm, 125nm, 130nm, 135nm, 140nm, 145nm or 150nm, etc., or it can be other values within the range of 50nm to 150nm. In some preferred embodiments, the thickness of each TCO film layer is 70nm to 120nm, such as 70nm, 72nm, 75nm, 78nm, 80nm, 82nm, 85nm, 88nm, 90nm, 92nm, 95nm, 98nm, 100nm, 102nm, 105nm, 108nm, 110nm, 112nm, 115nm, 118nm or 120nm, etc., and can also be other values within the range of 70nm to 120nm. In some more preferred embodiments, the thickness of each TCO film layer is 80nm to 100nm.
[0091] In some optional embodiments, the surface roughness of each TCO film layer on the side away from the battery substrate is 20nm to 30nm. It should be noted that the smaller the roughness of the TCO film layer, the larger the grain size. If the surface roughness of the TCO film layer on the side away from the battery substrate is less than 20nm, especially less than 2nm, there will be obvious gaps and large grain boundaries between the grains, which may easily cause copper atoms or ions to aggregate, and ultimately lead to a significant decrease in the overall performance of the TCO film layer.
[0092] In some optional embodiments, the concentration of copper in the 5 nm depth range of the TCO film layer from the surface of the TCO film layer to the battery substrate is 1×10 18 ions / cm 2 ~1×10 21 ions / cm 2 .
[0093] The doping concentration is 10 in the 5nm depth range of the TCO film layer along the direction from the surface of the TCO film layer to the battery substrate. 18 ions / cm 2 ~1×10 21 ions / cm 2The copper (copper is mainly doped in the form of atoms and / or ions) can form copper compounds or alloy phases, enhance chemical bonding, improve interface structure, and increase the bonding strength between the TCO film layer and the metal seed layer in the gate line area, thereby facilitating the bonding between the gate line and the battery substrate. The chemical bonds involved in the "bonding" in the present invention include ionic bonds and covalent bonds. For example, copper ions (Cu2+) can bond with oxygen atoms (O 2 -). This is because copper ions carry a positive charge, while oxygen atoms in oxides usually carry a negative charge, and they form a stable ionic bond through electrostatic attraction. This bonding effect is particularly significant when copper ions replace some indium ions or tin ions in ITO, which can maintain charge balance. For example, when copper atoms exist in a lower valence state (such as Cu+ or Cu), they can share electron pairs with indium or tin atoms to form covalent bonds.
[0094] In addition, the copper infiltrated into the TCO film layer can improve the density of the internal structure of the TCO film layer, and the copper located on the surface of the TCO film layer can play a protective role, blocking the erosion of the TCO film layer by corrosive substances and improving the corrosion resistance of the TCO film layer.
[0095] In the above, along the direction from the surface of the TCO film layer to the battery substrate, the present invention controls the concentration of copper in the 5nm depth range of the TCO film layer to 1×10 18 ions / cm 2 ~1×10 21 ions / cm 2 , which can not only largely not affect the integrity of the TCO film layer or grains (i.e., it will basically not damage the integrity of the TCO film layer structure), but also improve the bonding strength between the TCO film layer and the metal seed layer in the gate line area. If the copper doping concentration within the 5nm depth of the TCO film layer is less than 1×10 18 ions / cm 2 , it is difficult to effectively improve the bonding strength between the TCO film layer and the copper seed layer in the gate line area; if the copper doping concentration within the 5nm depth of the TCO film layer is higher than 1×10 21 ions / cm 2 On the one hand, the process is difficult to achieve, and on the other hand, it is difficult to maintain the integrity of the TCO film layer and grains, which may reduce the performance of the battery.
[0096] The effects of copper under the above-mentioned doping depth and doping concentration conditions on the bonding force between the TCO layer and the metal seed layer in the gate line region include: first, it can enhance chemical bonding, that is, during the copper doping process, copper atoms and / or copper ions will penetrate into the interface region between the TCO layer and the metal seed layer in the gate line region, and form new chemical bonds with adjacent atoms. The formation of these chemical bonds enhances the interaction between the TCO layer and the metal seed layer in the gate line region, thereby improving the bonding force between the TCO layer and the metal seed layer in the gate line region. Second, it can improve the interface structure. The doping of copper atoms and / or copper ions will change the microstructure of the film interface and reduce unfavorable factors such as pores and defects at the interface. Third, the doping of copper atoms and / or copper ions will introduce copper elements into the film layer to form copper compounds or alloy phases (such as copper-tin alloy, copper-indium alloy or copper-indium-tin alloy, etc.), which helps to increase the interface area, improve the interface energy, and thus enhance the bonding force between the film layers. Fourthly, the doping of copper atoms and / or copper ions can promote the mutual diffusion of elements between the TCO layer and the metal seed layer in the gate line area. This diffusion process helps to form a more uniform alloy layer or compound layer and enhance the bonding strength between film layers.
[0097] In some optional embodiments, the concentration of copper in the TCO film layer from the surface to the battery substrate is 1×10 10 ions / cm 2 ~1×10 14 ions / cm 2 , such as 1×10 10 ions / cm 2 , 5×10 10 ions / cm 2 , 1×10 11 ions / cm 2 , 5×10 11 ions / cm 2 , 1×10 12 ions / cm 2 , 5×10 12 ions / cm 2 , 1×10 13 ions / cm 2 , 5×10 13 ions / cm 2 or 1×10 14 ions / cm 2 etc., or 1×10 10 ions / cm 2 ~1×10 14 ions / cm 2 Other values within the range.
[0098] In some optional embodiments, the copper concentration in the TCO film layer from the surface to the battery substrate is ≤1×10 5 ions / cm 2 , such as 1×10 5 ions / cm 2 , 5×10 4 ions / cm 2 , 1×10 4 ions / cm 2 , 5×10 3 ions / cm 2 , 1×10 3 ions / cm 2 , 5×10 2 ions / cm 2 , 1×10 2 ions / cm 2 , 5×10 1 ions / cm 2 , 1×10 1 ions / cm 2 、0.5ions / cm 2 or 0.1ions / cm 2 etc., or ≤1×10 5 ions / cm 2 Other values within the range.
[0099] In some optional embodiments, the concentration of copper in the range of 25 nm to 30 nm in depth along the direction from the surface of the TCO film layer to the battery substrate can be 1×10 5 ions / cm 2 ~1×10 14 ions / cm 2 In other embodiments, in some optional embodiments, the concentration of copper in the depth range of 25nm to 30nm is ≤1×10 5 ions / cm 2 .
[0100] In some optional embodiments, the depth of copper in the TCO film layer does not exceed 50 nm along the direction from the surface of the TCO film layer to the battery substrate. In some other embodiments, the depth of copper in the TCO film layer does not exclude that it exceeds 50 nm, but after the depth exceeds 50 nm, no obvious copper element signal can be detected.
[0101] In some optional embodiments, the depth of copper in the TCO film layer from the surface of the TCO film layer to the battery substrate does not exceed 50 nm, and the concentration of copper within the 5 nm depth range is 1×1018 ions / cm 2 ~1×10 21 ions / cm 2 , the concentration in the depth range of 20nm to 25nm is 1×10 10 ions / cm 2 ~1×10 14 ions / cm 2 , the concentration in the depth range of 30nm to 50nm is less than 1×10 5 ions / cm 2 .
[0102] As mentioned above, the doping form and doping concentration of copper in the TCO film layer provided by the present invention can improve the conductivity and photoelectric response characteristics of the film layer while maintaining a high light transmittance, which is beneficial for the solar cell to have both better photoelectric conversion efficiency and conductivity.
[0103] In some optional embodiments, the thickness of the metal seed layer can be 30nm to 250nm, such as 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm, 115nm, 120nm, 125nm, 130nm, 135nm, 140nm The above-mentioned value may be any value within the range of 30nm to 250nm, or may be any other value within the range of 30nm to 250nm. In some preferred embodiments, the thickness of the metal seed layer is 50nm to 150nm, such as 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm, 115nm, 120nm, 125nm, 130nm, 135nm, 140nm, 145nm or 150nm, etc., and can also be other values within the range of 50nm to 150nm.
[0104] In some optional embodiments, an alloy layer exists between the interface of the metal seed layer and the corresponding TCO film layer, and the alloy contained in the alloy layer may include at least one of copper-tin alloy, copper-indium alloy and copper-indium-tin alloy according to different situations.
[0105] In some embodiments, the solar cell provided by the present invention includes a cell substrate;
[0106] A first passivation layer and a first doping layer are stacked on the front side of the battery substrate; a first TCO film layer is arranged on the front side of the doping layer, and a first metal seed layer is arranged on the front side of the first TCO film layer at a position corresponding to the gate line region; and a first gate line is connected to the front side of the first metal seed layer;
[0107] A second passivation layer and a second doping layer are stacked on the back of the battery substrate; a second TCO film layer is arranged on the back of the second doping layer, and a second metal seed layer is arranged on the back of the second TCO film layer at a position corresponding to the gate line area; and a second gate line is connected to the back of the second metal seed layer.
[0108] In some more specific embodiments, a solar cell includes a cell substrate;
[0109] A first intrinsic amorphous silicon layer and an N-type doped layer are stacked on the front of the battery substrate; a first TCO film layer is provided on the front of the N-type doped layer, and a first copper seed layer is provided on the front of the first TCO film layer at a position corresponding to the gate line area; and a first gate line is connected to the front of the first copper seed layer;
[0110] A second intrinsic amorphous silicon layer and a P-type doped layer are stacked on the back of the battery substrate; a second TCO film layer is provided on the back of the P-type doped layer, and a second copper seed layer is provided on the back of the second TCO film layer at a position corresponding to the gate line area; and a second gate line is connected to the back of the second copper seed layer.
[0111] Furthermore, the first copper gate line may be provided with a first protective layer, and the second gate line may be provided with a second protective layer.
[0112] It should be noted that in the actual design and preparation process, the structure of the solar cell can be increased, decreased and reasonably adjusted as needed. As long as the TCO film layer contains copper and at least 95% of the grains in the TCO film layer are in the range of 15nm to 35nm, the solar cell structure is within the scope of the present invention.
[0113] The solar cell provided by the present invention can have higher conversion efficiency, short-circuit current, fill factor, etc. than conventional solar cells, and the contact resistance between the grid line and the substrate is low. It can improve the conductivity and photoelectric response characteristics of the film layer while maintaining a high light transmittance, thereby achieving the effect of having both better photoelectric conversion efficiency and conductive performance.
[0114] Correspondingly, the present invention also provides a method for preparing the above solar cell, comprising the following steps: disposing a copper-containing TCO film layer on the first surface and / or the second surface of the cell substrate.
[0115] In some optional embodiments, the method for preparing a solar cell includes the following steps: disposing a copper-containing TCO film layer on the first surface and / or the second surface of the cell substrate;
[0116] A metal seed layer is arranged on the side of the TCO film layer away from the battery substrate; and the copper seed layer is connected to the gate line.
[0117] Furthermore, a protection layer is disposed on the surface of the gate line.
[0118] In some optional embodiments, the method for preparing a solar cell comprises the following steps:
[0119] A first passivation layer and a first doping layer are stacked on the first surface of the battery substrate; a first TCO film layer is disposed on the front of the first doping layer, and a first metal seed layer is disposed on the front of the first TCO film layer; and a first gate line is connected to the front of the first metal seed layer;
[0120] A second passivation layer and a second doping layer are stacked on the second surface of the battery substrate; a second TCO film layer is disposed on the back of the second doping layer, and a second metal seed layer is disposed on the back of the second TCO film layer; and a second gate line is connected to the back of the second metal seed layer.
[0121] In some specific embodiments, the method for preparing a solar cell comprises the following steps:
[0122] A first intrinsic amorphous silicon layer and an N-type doped layer are stacked on the front of the battery substrate; a first TCO film layer is disposed on the front of the N-type doped layer, and a first copper seed layer is disposed on the front of the first TCO film layer; and a first gate line is connected to the front of the first copper seed layer;
[0123] A second intrinsic amorphous silicon layer and a P-type doped layer are stacked on the back of the battery substrate; a second TCO film layer is disposed on the back of the P-type doped layer, and a second copper seed layer is disposed on the back of the second TCO film layer; and a second gate line is connected to the back of the second copper seed layer.
[0124] Furthermore, a first protective layer is disposed on the surface of the first copper grid line; and a second protective layer is disposed on the surface of the second grid line.
[0125] It should be noted that any method that can achieve the TCO film layer proposed by the present invention contains copper and at least 95% of the grains in the TCO film layer have a size of 15nm to 35nm is within the protection scope of the present invention. The present invention does not specifically limit the specific preparation conditions and methods, and only some of the implementation methods are listed below.
[0126] In some optional embodiments, the preparation of the TCO film layer includes: depositing the TCO film layer by PVD magnetron sputtering, followed by annealing.
[0127] The deposition power density used to prepare the TCO film layer can be 2.5 kw / m to 5.0 kw / m, such as 2.5 kw / m, 3.0 kw / m, 3.5 kw / m, 4.0 kw / m, 4.5 kw / m or 5.0 kw / m, or other values within the range of 2.5 kw / m to 5.0 kw / m. In some preferred embodiments, the deposition power density used to prepare the TCO film layer is 3.0 kw / m to 4.0 kw / m.
[0128] During the deposition of the TCO film, the temperature of the substrate may be 170° C. to 220° C., such as 170° C., 175° C., 180° C., 185° C., 190° C., 195° C., 200° C., 205° C., 210° C., 215° C. or 220° C., or other values within the range of 170° C. to 220° C. In some preferred embodiments, the temperature of the substrate is 190° C. to 210° C., such as 190° C., 192° C., 195° C., 198° C., 200° C., 202° C., 205° C., 208° C. or 210° C.
[0129] The annealing temperature used in preparing the TCO film layer may be 180° C. to 230° C., such as 180° C., 185° C., 190° C., 195° C., 200° C., 205° C., 210° C., 215° C., 220° C., 225° C. or 230° C., etc., or other values within the range of 180° C. to 230° C. In some preferred embodiments, the annealing temperature used in preparing the TCO film layer is 220° C.
[0130] The annealing time used to prepare the TCO film layer can be 5 min to 25 min, such as 5 min, 8 min, 10 min, 12 min, 15 min, 18 min, 20 min, 22 min or 25 min, etc., or other values within the range of 5 min to 25 min. In some preferred embodiments, the annealing time used to prepare the TCO film layer is 15 min.
[0131] Under the above conditions, a TCO film with higher crystallinity and larger grain size can be obtained, which is more conducive to preventing and improving the possible weakening of TCO optical properties after copper injection and avoiding the reduction of short-circuit current of the cell. In addition, it is also more conducive to improving the process window of copper electroplating and preventing the TCO film from being corroded by the acid solution of the copper electroplating process.
[0132] In some optional embodiments, the preparation of the metal seed layer includes: depositing a copper seed layer by PVD magnetron sputtering, followed by annealing.
[0133] The copper implantation energy for preparing the metal seed layer may be 300KeV to 1000KeV, such as 300KeV, 350KeV, 400KeV, 450KeV, 500KeV, 550KeV, 600KeV, 650KeV, 700KeV, 750KeV, 800KeV, 850KeV, 900KeV, 950KeV or 1000KeV, or other values within the range of 300KeV to 1000KeV. In some preferred embodiments, the copper implantation energy is 500KeV to 800KeV, such as 500KeV, 520KeV, 550KeV, 580KeV, 600KeV, 620KeV, 650KeV, 680KeV, 700KeV, 720KeV, 750KeV, 780KeV or 800KeV.
[0134] The deposition power density of the metal seed layer can be 3.0 kw / m to 6.0 kw / m, such as 3.0 kw / m, 3.5 kw / m, 4.0 kw / m, 4.5 kw / m, 5.0 kw / m, 5.5 kw / m or 6.0 kw / m, or other values within the range of 3.0 kw / m to 6.0 kw / m. In some preferred embodiments, the deposition power density of the copper seed layer can be 4.0 kw / m to 5.0 kw / m, such as 4.0 kw / m, 4.1 kw / m, 4.2 kw / m, 4.3 kw / m, 4.4 kw / m, 4.5 kw / m, 4.6 kw / m, 4.7 kw / m, 4.8 kw / m, 4.9 kw / m or 5.0 kw / m, etc.
[0135] During the deposition of the copper seed layer, the temperature of the substrate may be 160° C. to 230° C., such as 160° C., 165° C., 170° C., 175° C., 180° C., 185° C., 190° C., 195° C., 200° C., 205° C., 210° C., 215° C., 220° C., 225° C., or 230° C., or other values within the range of 160° C. to 230° C. In some preferred embodiments, the temperature of the substrate is 170° C. to 190° C., such as 170° C., 172° C., 175° C., 178° C., 180° C., 182° C., 185° C., 188° C., or 190° C., or the like.
[0136] The annealing temperature of the metal seed layer can be 170℃~250℃, such as 170℃, 175℃, 180℃, 185℃, 190℃, 195℃, 200℃, 205℃, 210℃, 215℃, 220℃, 225℃, 230℃, 235℃, 240℃, 245℃ or 250℃, etc., or it can be other values within the range of 170℃~250℃.
[0137] The annealing time of the metal seed layer may be 5 min to 25 min, such as 5 min, 8 min, 10 min, 12 min, 15 min, 18 min, 20 min, 22 min or 25 min, or may be other values within the range of 5 min to 25 min.
[0138] The annealing of the metal seed layer is carried out under vacuum conditions. High-temperature vacuum annealing can eliminate the internal stress between the TCO film layer and the metal seed layer, ensuring that the metal seed layer and the TCO film layer are directly and tightly bonded. In addition, the annealing process of the metal seed layer can, on the one hand, make the metal atoms and / or metal ions diffuse evenly in the TCO film layer and be injected into a deeper position, thereby improving the bonding ability; on the other hand, it can also prevent the metal seed layer from being oxidized.
[0139] In some of the above-mentioned embodiments proposed by the present invention, by first depositing a TCO film layer, then depositing a metal seed layer, and by setting relevant preparation conditions of the TCO film layer and the metal seed layer, a better metal atom and / or metal ion doping effect can be obtained in the TCO film layer. However, the method of directly doping the metal in the TCO target material for film coating is not excluded. However, when the metal is directly doped in the TCO target material for film coating, the metal in the target material mainly exists in the form of metal oxide, and when it is deposited on the surface of the silicon wafer, the metal inside the entire film layer also mainly exists in the form of metal oxide. In this method, the concentration of the metal is evenly distributed, and the effect of forming a specific structure with the top layer of the gate line is worse, and the effect of improving the gate line bonding force is worse than depositing the TCO film layer first and then depositing the metal seed layer.
[0140] It should be noted that the conventional processes not further described and described in detail above can all refer to the relevant existing technologies and will not be described in detail here.
[0141] The following is a more specific implementation example, and the preparation of the solar cell involved in this implementation example can refer to the following steps:
[0142] (1) Texturing and cleaning: Texturing and cleaning the battery substrate to form a positive pyramid structure on the surface of the silicon wafer (the size of the pyramid structure may be, for example, 2 μm to 8 μm, preferably 3 μm to 6 μm);
[0143] (2) using PECVD plasma deposition equipment to deposit an amorphous silicon film on the battery substrate after texturing and cleaning (wherein the thickness of the intrinsic amorphous silicon layer on the front side can be 3nm to 6nm, the thickness of the intrinsic amorphous silicon layer on the back side can be 5nm to 10nm, the thickness of the N-type doped layer on the front side can be 5nm to 10nm, and the thickness of the P-type doped layer on the back side can be 5nm to 15nm);
[0144] (3) PVD-TCO deposition: a TCO film layer is deposited on the surface of the amorphous silicon film layer by a PVD magnetron sputtering device (the thickness of the TCO film layer may be 50 nm to 150 nm, preferably 70 nm to 120 nm, and more preferably 80 nm to 100 nm), the deposition power density of the TCO film layer is 2.5 kw / m to 5.0 kw / m (preferably 3.0 kw / m to 4.0 kw / m), and the temperature of the substrate is kept at 170°C to 220°C (preferably 190°C to 210°C) during the deposition process; after the deposition is completed, annealing is performed at 180°C to 230°C (preferably 220°C) for 5 min to 25 min (preferably 15 min);
[0145] (4) PVD-Cu (copper seed layer) deposition: A copper seed layer is deposited on the surface of the TCO film layer using a PVD magnetron sputtering device (the thickness of the copper seed layer can be 30 nm to 250 nm, preferably 50 nm to 150 nm), the copper injection energy is 300 KeV to 1000 KeV (preferably 500 KeV to 800 KeV), the deposition power density is 3.0 kw / m to 6.0 kw / m (preferably 4.0 kw / m to 5.0 kw / m), and the temperature of the substrate is kept at 160°C to 230°C (preferably 170°C to 190°C) during the deposition process; after the deposition is completed, annealing is performed at 170°C to 250°C and 0.1 mbar to 2.0 mbar for 5 min to 25 min to obtain a yellow film.
[0146] (5) Coating: Coating the surface of the yellow film with photosensitive ink to completely cover the copper seed layer (the coating thickness of the photosensitive ink can be 10 μm to 15 μm);
[0147] (6) Laser printing: The predetermined pattern is printed on the photosensitive film by laser according to the designed grid line pattern, and the photosensitive film undergoes photosensitive property change to distinguish it from the unphotosensitive area;
[0148] (7) Development: Use an alkaline solution (such as sodium carbonate solution) to clean and remove the photosensitive ink area, forming a groove on the battery surface and exposing the underlying copper seed layer;
[0149] (8) electroplating: electroplating copper grid lines in a first electroplating solution (such as a copper sulfate solution, etc.), and the height of the copper grid lines can be 6 μm to 12 μm; electroplating a tin protective layer in a second electroplating solution (such as a tin methanesulfonate solution, etc.), and the height of the tin protective layer can be 2 μm to 6 μm;
[0150] (9) Film stripping and etching back: First, remove all the photosensitive ink in an alkaline solution (such as NaOH solution and / or KOH solution, etc.), then remove the copper seed layer in the non-gate line area in an acid solution (such as dilute sulfuric acid solution, etc.), and finally leave the gate line on the surface of the TCO film layer;
[0151] (10) performing light injection treatment on the cell after film stripping and back engraving (the light injection temperature can be 200° C. to 220° C., and the time can be 60s to 120s);
[0152] (11) Complete the battery cell production and conduct IV test on electrical performance.
[0153] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0154] Example 1
[0155] This embodiment provides a solar cell. Figure 1 , Figure 4 and Figure 5 , the solar cell comprises a cell substrate 100 (silicon wafer);
[0156] The front side of the battery substrate 100 is stacked with a first intrinsic amorphous silicon layer 111 and an N-type doped layer 112, the front side of the N-type doped layer 112 is provided with a first TCO film layer 113, and the front side of the first TCO film layer 113 is provided with a first copper seed layer 114; the front side of the first copper seed layer 114 is connected with a first gate line 115 (copper gate line); the surface of the first gate line 115 is provided with a first protective layer 116 (tin protective layer);
[0157] A second intrinsic amorphous silicon layer 121 and a P-type doped layer 122 are stacked on the back of the battery substrate 100; a second TCO film layer 123 is provided on the back of the P-type doped layer 122, and a second copper seed layer 124 is provided on the back of the second TCO film layer 123; a second gate line 125 (copper gate line) is connected to the back of the second copper seed layer 124; and a second protective layer 126 (tin protective layer) is provided on the surface of the second gate line 125.
[0158] Among them, along the direction from the surface of the TCO film layer to the battery substrate 100, the 5nm depth range of the TCO film layer (such as Figure 5 In the depth region (①), the copper concentration is 1×10 18 ions / cm 2 ~1×10 21 ions / cm 2 ; TCO film layer 20nm ~ 25nm depth range (such as Figure 5 In the depth region (2), the copper concentration is 1×10 10 ions / cm 2 ~1×10 14 ions / cm 2 , the depth range of TCO film is 30nm~50nm (such as Figure 5 In the depth area (3), the copper concentration is ≤1×10 5ions / cm 2 ; No obvious signal can be detected when the depth of copper in the TCO film layer exceeds 50nm.
[0159] Please refer to Figure 2 and Figure 3 The first TCO film layer 113 and the second TCO film layer 123 both have <222> , <211> , <400> , <332> , <440> as well as <622> Grain orientation. Among them, <222> The intensity of the first diffraction peak corresponding to the grain orientation is the strongest. <622> The intensity of the seventh diffraction peak corresponding to the grain orientation is the third. In the first TCO film layer 113, <440> The intensity of the fourth X-ray diffraction peak corresponding to the grain orientation is approximately <222> The intensity of the first X-ray diffraction peak corresponding to the grain orientation is 1 / 3, <622> The intensity of the seventh X-ray diffraction peak corresponding to the grain orientation is approximately <222> 1 / 6 of the intensity of the first X-ray diffraction peak corresponding to the grain orientation. In the first TCO film layer 113, the intensity of the seventh X-ray diffraction peak is greater than the intensity of the fourth X-ray diffraction peak; in the second TCO film layer 123, the intensity of the seventh X-ray diffraction peak is less than the intensity of the fourth X-ray diffraction peak. More than 99% of the grains in the first TCO film layer 113 and the second TCO film layer 123 have a size of 18nm to 25nm. Among them, <222> The grain orientation accounts for about 75wt%, except <222> , <440> as well as <622> The total proportion of other grains other than the grains corresponding to the grain orientation in each TCO film layer is about 2 wt %.
[0160] The thickness of the first TCO film layer 113 and the second TCO film layer 123 are both 100 nm, the thickness of the first copper seed layer 114 and the second copper seed layer 124 are both 100 nm, the surface roughness of the first TCO film layer 113 on the side away from the battery substrate 100 is 25 nm, and the surface roughness of the second TCO film layer 123 on the side away from the battery substrate 100 is also 25 nm.
[0161] Example 2
[0162] The difference between this embodiment and embodiment 1 is that: in the first TCO film layer, <440> The intensity of the fourth X-ray diffraction peak corresponding to the grain orientation is approximately <222> The intensity of the first X-ray diffraction peak corresponding to the grain orientation is 1 / 5, <622> The intensity of the seventh X-ray diffraction peak corresponding to the grain orientation is approximately <222> The intensity of the first X-ray diffraction peak corresponding to the grain orientation is 1 / 6. More than 97% of the grains in the first TCO film layer and the second TCO film layer have a size of 18nm to 25nm. <222> The grain orientation accounts for about 70wt%, except <222> , <440> as well as <622> The total proportion of other grains other than the grains corresponding to the grain orientation in each TCO film layer is about 10 wt %.
[0163] Example 3
[0164] The difference between this embodiment and embodiment 1 is that: in the first TCO film layer, <440> The intensity of the fourth X-ray diffraction peak corresponding to the grain orientation is approximately <222> The intensity of the first X-ray diffraction peak corresponding to the grain orientation is 1 / 6, <622> The intensity of the seventh X-ray diffraction peak corresponding to the grain orientation is approximately <222> The intensity of the first X-ray diffraction peak corresponding to the grain orientation is 1 / 6. More than 98% of the grains in the first TCO film layer and the second TCO film layer have a size of 18nm to 25nm. <222> The grains with grain orientation account for about 80wt%, except <222> , <440> as well as <622> The total proportion of other grains other than the grains corresponding to the grain orientation in each TCO film layer is about 5 wt %.
[0165] Example 4
[0166] The difference between this embodiment and embodiment 1 is that: in the TCO film layer, <222> The grain-oriented grains account for 60 wt%.
[0167] Example 5
[0168] The difference between this embodiment and embodiment 1 is that: in the TCO film layer, <222> The grain-oriented grains account for 90 wt%.
[0169] Example 6
[0170] The difference between this embodiment and embodiment 1 is that: <222> Grain orientation, <440> Grain orientation and <622> The total proportion of grains corresponding to the grain orientation in the TCO film layer is 80wt%.
[0171] Example 7
[0172] This embodiment provides a method for preparing the solar cell of embodiment 1, comprising the following steps:
[0173] (1) Texturing and cleaning: Texturing and cleaning the silicon wafer substrate to form a positive pyramid structure on the surface of the silicon wafer (the size of the pyramid structure is 4 μm);
[0174] (2) using PECVD plasma deposition equipment to deposit a first intrinsic amorphous silicon layer and an N-type doped layer on the front side of the substrate after texturing and cleaning, and to deposit a second intrinsic amorphous silicon layer and a P-type doped layer on the back side of the substrate (wherein the thickness of the first intrinsic amorphous silicon layer is 6 nm, the thickness of the second intrinsic amorphous silicon layer is 9 nm, the thickness of the N-type doped layer is 10 nm, and the thickness of the P-type doped layer is 15 nm);
[0175] (3) PVD-TCO deposition: A PVD magnetron sputtering device is used to deposit a first TCO film layer on the surface of the N-type doped layer, and a second TCO film layer is deposited on the surface of the P-type doped layer (the thickness of each TCO film layer is 100 nm). The deposition power density of each TCO film layer is 4.0 kW / m. During the deposition process, the temperature of the substrate is kept at 210°C. After the deposition, annealing is performed at 220°C for 15 min.
[0176] (4) PVD-Cu (copper seed layer) deposition: A first copper seed layer was deposited on the surface of the first TCO film layer, and a second copper seed layer was deposited on the surface of the second TCO film layer using a PVD magnetron sputtering device (the thickness of each copper seed layer was 100 nm). The copper injection energy was 800 KeV, and the deposition power density was 4.0 kW / m. During the deposition process, the substrate temperature was kept at 180°C. After the deposition, the substrate was annealed at 250°C and a vacuum degree of 1.0 mbar for 15 min to obtain a yellow film.
[0177] (5) Coating: Coat the surface of the yellow film with photosensitive ink to completely cover the copper seed layer (the coating thickness of the photosensitive ink is 12 μm);
[0178] (6) Laser printing: The predetermined pattern is printed on the photosensitive film by laser according to the designed grid line pattern, and the photosensitive film undergoes photosensitive property change to distinguish it from the unphotosensitive area;
[0179] (7) Development: Use an alkaline solution (sodium carbonate solution) to clean and remove the photosensitive ink area, forming a groove on the battery surface and exposing the underlying copper seed layer;
[0180] (8) electroplating: electroplating a copper grid line in a first electroplating solution (copper sulfate solution), with the copper grid line height being 9 μm; electroplating a tin protective layer in a second electroplating solution (tin methanesulfonate solution), with the tin protective layer height being 4 μm;
[0181] (9) Film stripping and etching: First, remove all the photosensitive ink in an alkaline solution (NaOH solution), then remove the copper seed layer in the non-gate line area in an acid solution (dilute sulfuric acid solution), and finally leave the gate line on the surface of the TCO film layer;
[0182] (10) The cell after film stripping and re-etching is subjected to light injection treatment (the light injection temperature is 210° C. and the time can be 90 seconds) to complete the cell production.
[0183] Comparative Example 1
[0184] The difference between this embodiment and embodiment 1 is that the size of 95% of the grains in each TCO film layer is less than 15 nm.
[0185] Comparative Example 2
[0186] The difference between this embodiment and embodiment 1 is that the size of 95% of the grains in each TCO film layer is greater than 35 nm.
[0187] Test Example 1
[0188] The solar cells prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were subjected to performance tests. The test results are shown in Tables 1 and 2. The data are average values obtained from 5 parallel tests.
[0189] Table 1 Test results
[0190]
[0191] It can be seen from Table 1 that:
[0192] The bonding strength and electrical parameter performance of the solar cells prepared in Examples 1 to 3 are better than those in Examples 4 to 6 and Comparative Examples 1 to 2, and Examples 4 to 6 are better than Comparative Examples 1 to 2, indicating that the grain characteristics of the TCO film layer will affect the bonding strength between the TCO film layer and the copper seed layer in the gate line area and the electrical parameters of the solar cell, and that it is not a simple setting that can have both better bonding strength and electrical parameters.
[0193] Among them, it can be concluded from the comparison between Example 1 and Comparative Examples 1 to 2 that improper grain size in the TCO film layer will significantly affect the bonding strength and electrical parameters of the solar cell. The reasons include: the grain size in the TCO film layer indirectly affects the concentration of copper injected into the TCO film layer by affecting the number of grain boundaries, carrier transport and film quality. By controlling at least 95% of the grain size in the TCO film layer to be 15nm to 35nm, under this grain size and content, it is possible to ensure the effective doping of copper in the TCO film layer while avoiding excessive accumulation of copper at the grain boundaries, thereby effectively improving the bonding strength between the gate line and the TCO film layer while ensuring that the TCO film layer has excellent overall performance.
[0194] From the comparison between Example 1 and Examples 4-5, it can be seen that in the TCO film layer, <222> If the proportion of grains with grain orientation is too low or too high, it will affect the bonding strength and electrical parameters of solar cells. <222> When the grain proportion of grain orientation meets the range of 70wt% to 80wt%, the solar cell can have higher bonding strength and better overall electrical parameters. The reasons include: <222> When the proportion of grains with grain orientation meets the condition of 70wt% to 80wt%, on the one hand, the uniformity of copper doping can be improved, and on the other hand, the damage to the light transmission performance of TCO can be minimized. In addition, it is also beneficial to improve the conductivity of the TCO film layer.
[0195] From the comparison between Example 1 and Example 6, it can be seen that in the TCO film layer, <222> Grain orientation, <440> Grain orientation and <622> The total proportion of grains corresponding to the grain orientation in the TCO film layer will also affect the bonding strength and electrical parameters of the solar cell; when the total proportion of the above three grain orientations in the TCO film layer is not less than 90wt%, the solar cell can have a higher bonding strength and better overall electrical parameters. The reasons include: <222> Grain orientation, <440> Grain orientation and <622> The total proportion of grains corresponding to the grain orientation in the TCO film layer is controlled to be no less than 90wt%, which can facilitate the injection of copper; at the same time, it is also beneficial to prevent and improve the possible weakening of the optical properties of TCO after copper injection, and avoid the reduction of the short-circuit current of the battery cell.
[0196] Test Example 2
[0197] Taking the yellow film prepared in Example 7 as an example, the yellow film sample was immersed in an acid solution (made of water and sulfuric acid, with a sulfuric acid concentration of 5%) for 10 minutes. The results after immersion are as follows: Figure 6 As shown by Figure 6 It can be seen that the yellow film sheet prepared in the embodiment of the present invention was not corroded after being soaked in the above acidic solution, and the TCO film layer did not fall off, indicating that the solution provided by the present invention can improve the corrosion resistance of the TCO film layer.
[0198] In summary, the solar cell provided by the present invention can improve the corrosion resistance, conductivity and photoelectric response characteristics of the film layer while maintaining a high light transmittance, which is beneficial for the solar cell to have both better photoelectric conversion efficiency and conductivity.
[0199] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A solar cell, characterized in that: The solar cell comprises a cell substrate, wherein the cell substrate comprises a first surface and a second surface opposite to the first surface; It also includes a TCO film layer located on the first surface and / or the second surface, wherein the TCO film layer contains copper; at least 95% of the grains in the TCO film layer have a size of 15nm to 35nm.
2. The solar cell according to claim 1, characterized in that: The TCO film layer contains at least <222> Grain orientation; and, in the TCO film layer, <222> The intensity of the diffraction peak corresponding to the grain orientation is the strongest.
3. The solar cell according to claim 2, characterized in that: In the TCO film layer, <222> The grain-oriented grains account for 70 wt% to 80 wt%.
4. The solar cell according to claim 2, characterized in that: The TCO film layer also contains <440> Grain orientation and <622> Grain orientation; Said <222> Grain orientation, <440> Grain orientation and the <622> The total proportion of grains corresponding to the grain orientation in the TCO film layer is not less than 90wt%.
5. The solar cell according to claim 4, characterized in that In the TCO film layer, <440> The diffraction peak intensity corresponding to the grain orientation is <222> 1 / 6 to 1 / 3 of the diffraction peak intensity corresponding to grain orientation; or, <622> The diffraction peak intensity corresponding to the grain orientation is <222> The diffraction peak intensity corresponding to the grain orientation is 1 / 6 to 1 / 3.
6. The solar cell according to claim 1, characterized in that Along the direction from the surface of the TCO film layer to the battery substrate, within the 5nm depth range of the TCO film layer, the concentration of copper is 1×10 18 ions / cm 2 ~1×10 21 ions / cm 2 ; Or, along the direction from the surface of the TCO film layer to the battery substrate, within the depth range of 20nm to 25nm of the TCO film layer, the concentration of copper is 1×10 10 ions / cm 2 ~1×10 14 ions / cm 2 ; Or, along the direction from the surface of the TCO film layer to the battery substrate, within the depth range of 30nm to 50nm of the TCO film layer, the concentration of copper is ≤1×10 5 ions / cm 2 ; Alternatively, along the direction from the surface of the TCO film layer to the battery substrate, the depth of copper in the TCO film layer does not exceed 50 nm.
7. The solar cell according to claim 1, characterized in that The surface roughness of the TCO film layer on a side away from the battery substrate is 20 nm to 30 nm.
8. The solar cell according to claim 1, characterized in that At least the grain boundary gaps in the TCO film layer are bonded with copper through bonding.
9. The solar cell according to claim 1, characterized in that: The thickness of the TCO film layer is 50nm-150nm.
10. The solar cell according to claim 1, characterized in that: A metal seed layer is disposed at a position corresponding to the gate line region on one side of the TCO film layer away from the battery substrate.
11. The solar cell according to claim 10, characterized in that The solar cell further comprises a doping layer arranged between the cell substrate and the TCO film layer, and a grid line connected to the metal seed layer.
12. The solar cell according to claim 11, characterized in that: The solar cell comprises a cell matrix; The front side of the battery substrate is stacked with a first passivation layer and a first doping layer; the front side of the doping layer is provided with a first TCO film layer, and the front side of the first TCO film layer is provided with a first metal seed layer at a position corresponding to the gate line area; the front side of the first metal seed layer is connected to the first gate line; A second passivation layer and a second doping layer are stacked on the back of the battery substrate; a second TCO film layer is provided on the back of the second doping layer, and a second metal seed layer is provided on the back of the second TCO film layer at a position corresponding to the gate line area; and a second gate line is connected to the back of the second metal seed layer.
13. A method for preparing a solar cell according to any one of claims 1 to 12, characterized in that: The following steps are involved: A copper-containing TCO film layer is disposed on the first surface and / or the second surface of the battery substrate.
14. The preparation method according to claim 13, characterized in that: The following steps are involved: Disposing a copper-containing TCO film layer on the first surface and / or the second surface of the battery substrate; A metal seed layer is disposed on a side of the TCO film layer away from the battery substrate.
15. The preparation method according to claim 14, characterized in that: The following steps are involved: A first passivation layer and a first doping layer are stacked on the first surface of the battery substrate; a first TCO film layer is disposed on the front of the first doping layer, and a first metal seed layer is disposed on the front of the first TCO film layer; a first gate line is connected to the front of the first metal seed layer; A second passivation layer and a second doping layer are stacked on the second surface of the battery substrate; a second TCO film layer is disposed on the back of the second doping layer, and a second metal seed layer is disposed on the back of the second TCO film layer; and a second gate line is connected to the back of the second metal seed layer.
Citation Information
Cited By
Solar cell and preparation method therefor
WO2026157505A1